Persistent Mullerian Duct Syndrome presenting as irreducible inguinal hernia - A surprise surgical finding! - V. Sekhon; M. Luthra; G. Jevalikar (Elsevier, 2017)
Persistent Mullerian Duct Syndrome (PMDS) is diagnosed as a discrepancy between masculine external genitalia and female internal genitalia during surgery for cryptorchidism or inguinal hernia. Approximately 200 cases have been reported in the literature so far, most of whom are adults. We discuss the management in an infant presenting with irreducible inguinal hernia with contralateral undescended testis.